Impact of center-volume on outcomes in myocardial infarction complicated by cardiogenic shock – a CULPRIT-SHOCK sub-study. (14th October 2021) - Clemmensen, P; Schrage, B N; Zeymer, U; Montalecot, G; Windecker, S; Serpytis, P; Stepinska, J; Savonitto, S; Desch, S; Fuernau, G; Huber, K; Noc, M; et al.
Abstract: Background: Little is known about the impact of center-volume on outcomes in acute myocardial infarction complicated by cardiogenic shock (AMI-CS). The aim of this study was to investigate the association between center-volume, treatment strategies and subsequent outcome in patients with AMI-CS. Methods: In this subanalysis of the randomized CULPRIT-SHOCK trial, study sites were categorized based on the annual volume of AMI-CS into low/intermediate/high volume centers (<50; 50–100;>100 cases/year). Subjects from the study/compulsory registry with available volume data were included. Baseline/procedural characteristics, overall treatment and 1-year all-cause mortality were compared across categories. Results: N=1032 patients were included in this study (537 treated at low-volume, 240 at intermediate-volume and 255 at high volume centers). Baseline risk profile of patients across the volume categories was similar, although high volume centers included more older patients. Low/intermediate-volume centers had more resuscitated patients (57.5%/58.8% vs. 42.2%; p<0.01), and more patients on mechanical ventilation in comparison to high volume centers. Mechanical circulatory support differed with more use in low/intermediate-volume centers and overall lower use in high-volume centers (30.7%/36.7% vs. 19.2%; p<0.001). There were no differences in reperfusion success despite considerable differences in adjunctive pharmacological/device therapies (figure 1). There was no difference in 1-year all-cause mortality across volume categories (51.1% vs. 56.5% vs. 54.4%; p=0.34). Conclusion: In this study of patients with AMI-CS, considerable differences in adjunctive medical and mechanical support therapies was observed. However, we could not detect an impact of center volume on reperfusion success or mortality. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): The CULPRIT-SHOCK trial was funded by European Union, Seventh Framework Programme (FP7/2007-2013) Grant agreement n°602202, German Heart Research Foundation